The Attitudes of Generation Y Tourists toward the Selfie Culture on Social Media - Dee-aim, Teerapattara; Yaemjamuang, Benjaporn; Rattanaprayoon, Sasithorn; Meesawatdikul, Weeraya; Dabphet, Siripen (Academic and Research Journal of Liberal Arts (Online), 2021)
Selfies became a global phenomenon on social media. Taking, posting, and viewing selfies while traveling has become a habit for many Generation Y tourists. However, there are no research studies which lead tourists to take selfies. This research investigates the attitudes of Generation Y tourists to selfies on social media. A quantitative research was used with a sample of 400 Generation Y tourists in various tourist destinations in Thailand. Descriptive statistics was used to describe the demographic characteristics of the tourists and factor analysis was used to examine tourists’ attitudes toward selfies on social media. The findings revealed seven attitudes toward selfies among Generation Y tourists: displaying status symbol, bragging about traveling, expression of identity, negative opinions toward selfies, following trends, social communication, and privacy concerns. The results of this study are useful for multi-sector stakeholders; both social media applications and the tourism industry can utilize the results of selfie behavior in business which will make them understand more of Generation Y tourists.